Polemical Note on Marcus, Golan, and Goodman. Ethical Issues Related to End of Life Treatment in Patients with Advanced Dementia – The Case of Artificial Nutrition and Hydration - Biondi, Paolo (Diametros, 2016)
This polemical note looks at the ethical issue of providing artificial nutrition and hydration (ANH) to patients with advanced dementia from the perspective of an Aristotelian and naturalist ethics. I argue that this issue may be considered in terms of the Aristotelian notion of eudaimonia, well-being. I present a number of facts about the conditions of human life that contribute to eudaimonia. In addition, I present a number of facts about advanced dementia as well as clarify the goals of medicine. From these facts, I argue that we are not ethically obligated to provide ANH to this class of patients.